Quantification of lipid bodies in monocytes from patients with periodontitis - Priscilla F. Naiff; Selma A. S. Kuckelhaus; Danilo Corazza; Luciana M. Leite; Shirley Couto; Mariangela S. deOliveira; Luander M. Santiago; Larissa F. Silva; Laudimar A. Oliveira; Daniela C. Grisi; Valeria M. A. Carneiro; Maria do C. M. Guimarães (Wiley, 2021)
Abstract Objectives For the first time in the history of periodontics, the production of lipid bodies by monocytes was assessed from blood of patients with periodontitis in comparison to systemically healthy individuals. The purpose of this study was to compare the lipid body frequency within monocytes between healthy patients and those with periodontal disease. Materials and Methods A total of 30 participants (11 males and 19 females), were divided between orally healthy control subjects (C, n = 16) and periodontitis subjects (P, n = 14), in a cross‐sectional study. Both groups were systemically healthy. The following clinical periodontal parameters were assessed: probing depth, clinical attachment level, visible plaque index and gingival bleeding on probing index. Blood samples were collected to obtain monocytes containing lipid bodies, which were analyzed by light microscopy. Results The periodontitis group demonstrated a higher corpuscular index than the control group (nonopsonized p = .0296 or opsonized p = .0459; Mann-Whitney). The frequency of monocyte cells containing lipid bodies (basal p = .0147, opsonized p = .0084 or nonopsonized, p = .026; Mann-Whitney) was also higher compared to those observed in healthy individuals. Conclusions The data suggest that periodontitis may contribute to a higher production of lipid bodies. It was also hypothesized that a major production of lipid bodies by monocytes in severe periodontitis, compared to orally healthy subjects, could interfere with the innate immune response or represents a higher reservoir of cholesterol esters within macrophages and a major risk to systemic implications, such as atherosclerosis.